Bay of Pigs: How groupthink led to a military failure - Carroll, John S. (Henry Stewart Talks, 2018)
This case study examines the Bay of Pigs crisis in 1961 and the inadequate decision-making process that led to failure. The US national security council succumbed to groupthink which manifested itself in an illusion of invulnerability and unanimity; and resulted in few alternatives and objectives being considered, a disregard for the risks involved and weak contingency planning.